Measurement of neutron production in atmospheric neutrino interactions at the Sudbury Neutrino Observatory - Aharmim, Bassam; Dunford, Monica (Physical review, 2019)
Neutron production in giga electron volt-scale neutrino interactions is a poorly studied process.We have measured the neutron multiplicities in atmospheric neutrino interactions in the SudburyNeutrino Observatory experiment and compared them to the prediction of a Monte Carlo simulationusinggenieand a minimally modified version ofgeant4. We analyzed 837 days of exposurecorresponding to Phase I, using pure heavy water, and Phase II, using a mixture of Cl in heavywater. Neutrons produced in atmospheric neutrino interactions were identified with an efficiencyof 15.3% and 44.3%, for Phases I and II respectively. The neutron production is measured asa function of the visible energy of the neutrino interaction and, for charged current quasielasticinteraction candidates, also as a function of the neutrino energy. This study is also performed byclassifying the complete sample into two pairs of event categories: charged current quasielastic andnon charged current quasielastic, andνμandνe. Results show good overall agreement between dataand Monte Carlo for both phases, with some small tension with a statistical significance below 2σfor some intermediate energies.